Discrete truncation method for measuring the cardiac t2* values in patients with thalassemia - Jixing Yi; Fengming Xu; Qing Feng; Bumin Liang; Jianli Qin; Hongfeng Liang; Haohua Wu; Ling Chen; Tao Li (Annals of Medicine)
Objective In clinical work, it has been found that there are differences between the dark-blood (DB) and bright-blood (BB) cardiac magnetic resonance (CMR) T2* values (DB-T2* and BB-T2*) measured by the current automatic truncation method in patients with cardiac iron overload. The paper aims to develop a novel discrete truncation method to measure cardiac T2* value in patients with thalassemia.Methods The cardiac T2* values of 349 thalassemia (TM) patients (mean age, 13.41 years ±8.761, 173 males) from three hospitals during January 2011 to June 2023 were measured by CMRtools software. Different truncation methods were used to remove signal values that deviated from the fitting curve and the corresponding T2* values were recorded. The difference, correlation and consistency of DB-T2* and BB-T2* measured by different methods were compared.Results There was no significant difference between DB-T2* and BB-T2* measured by discrete truncation method (DB-T2* vs.BB-T2*, p = 0.249), respectively; and there was a high positive correlation (rs = 0.997, p < 0.0001). In the Bland-Altman analysis, the two methods had a very good agreement (p = 0.2489). There was a high positive correlation between DB-T2* and BB-T2* measured by the automatic truncation method (rs = 0.974, p < 0.0001), but there was a significant difference between them (DB-T2* vs.BB-T2*, p < 0.0001), respectively. In the Bland-Altman analysis, there was no good agreement between the two methods (p < 0.0001).Conclusion The discrete truncation method is more stable and reliable than the automatic truncation method in the measurement of cardiac T2* value in TM patients.